If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -2) + (x + 6) = 0 Reorder the terms: (-2 + x) + (x + 6) = 0 Remove parenthesis around (-2 + x) -2 + x + (x + 6) = 0 Reorder the terms: -2 + x + (6 + x) = 0 Remove parenthesis around (6 + x) -2 + x + 6 + x = 0 Reorder the terms: -2 + 6 + x + x = 0 Combine like terms: -2 + 6 = 4 4 + x + x = 0 Combine like terms: x + x = 2x 4 + 2x = 0 Solving 4 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 2x = 0 + -4 2x = 0 + -4 Combine like terms: 0 + -4 = -4 2x = -4 Divide each side by '2'. x = -2 Simplifying x = -2
| 1.5x=425 | | 7x^2=5-5x | | 3x-5x(x-5)=-7+5x-24 | | 850/2= | | -5(-x-1)+2=x+19 | | 4[2(21-17)+3]= | | (X-5)=(-4) | | -4x+2(-x-1)=-2x+2 | | s+2.5s+10=38 | | a/8-12-3=-12 | | 0.75+0.25m=0.75-0.25 | | X+9=18-3x | | -6t+5+2t-9= | | -2(-x+2)-4x-4=3x+2 | | -2j(j-3)=-2j+6 | | 10x^2-160=0 | | s+2.5s+20=40 | | 4(2(21-17)+3)= | | -8x=3x+2 | | 49a^2-121=0 | | -4n-(8-4n)=4+2n | | 2d-5=32 | | -5x-4=-5x+3 | | 16y-27=13y | | .70x+5=19 | | 57-x-3(x+3)=0 | | -x+5=-4x+5 | | y=-6(x+2)+16 | | 3(7x-9)-19x=15 | | x+3=-2x-3 | | 3-2+x= | | 4(x-6)+6=6x-6 |